Decrease in ADAR1 expression by exposure to cigarette smoke enhances susceptibility to oxidative stress. (1st October 2020) - Takizawa, Masashi; Nakano, Masataka; Fukami, Tatsuki; Nakajima, Miki
Graphical abstract: Highlights: Cigarette smoke extract (CSE) decreases the expression of ADAR1, catalyzing A-to-I RNA editing. The decrease of ADAR1 is owing to the activated autophagy by CSE. ADAR1 contributes to the enhanced intracellular oxidative stress caused by cigarette smoking. Abstract: Adenosine-to-inosine (A-to-I) RNA editing, catalyzed by adenosine deaminase acting on RNA (ADAR) enzymes, is the most frequent type of post-transcriptional nucleotide conversion in humans. It is known that innate abnormalities of A-to-I RNA editing are associated with the risk of certain diseases, such as amyotrophic lateral sclerosis. Extrinsic factors that modulate ADAR-mediated RNA editing remain to be clarified. In this study, we investigated the possibility that cigarette smoking may influence the expression of ADAR and that the changes may be biologically significant. Treatment of human lung adenocarcinoma A549 cells with cigarette smoke extract (CSE) induced a significant 50% decrease in ADAR1 protein levels. Since the decrease was counteracted by cotreatment with chloroquine, the CSE-dependent decrease in the ADAR1 protein levels may be due to the activation of autophagy. In addition to the in vitro study, we performed an in vivo study in mice and found a decrease in pulmonary Adar1 protein expression induced by cigarette smoking. Then, we investigated the biological significance of decreased ADAR1 expression. We found that knockdown of ADAR1 in A549 cells by siRNA resulted in an increase in the levels of protein carbonyl, a marker of oxidative stress. Moreover, knockdown of ADAR1 triggered a decrease in super oxide dismutase activity and heme oxygenase-1 expression, suggesting that ADAR1 plays a role to suppress oxidative stress. In conclusion, we show that ADAR1 expression is decreased by cigarette smoking and is a factor that contributes to the enhanced intracellular oxidative stress caused by cigarette smoking.